Adverse drug reactions of GLP-1 agonists: A systematic review of case reports. Issue 3 (March 2022) - Shetty, Rashmi; Basheer, Fathima Thashreefa; Poojari, Pooja Gopal; Thunga, Girish; Chandran, Viji Pulikkel; Acharya, Leelavathi D.
Abstract: Background and aim: The importance of glucagon-like peptide-1 (GLP-1) agonists is increasing because of its blood sugar controlling and weight loss properties. The data regarding safety of GLP-1 agonists are limited. This study aims to review case reports and case series on adverse drug reactions (ADRs) of GLP-1 agonist. Methodology: A comprehensive search was performed in PubMed/Medline, Scopus and Embase to identify literatures. Bibliographic search and open search in Google, Google Scholar, SpringerLink and ResearchGate was performed to identify additional studies. Case reports and case series published the ADRs by the use of GLP-1 agonists in type 2 diabetes patients were included in the study. Reviews, experimental studies, observational studies, grey literature and non English studies were excluded. Results: The study identified 120 cases of GLP-1 agonists associated ADRs (liraglutide – 46, exenatide – 46, dulaglutide – 20, semaglutide – 4, albiglutide – 2, lixisenatide – 2). The major ADRs reported was gastrointestinal disorders (n = 40) followed by renal (n = 23), dermatologic (n = 14), hepatic (n = 10), immunologic (n = 13), endocrine/metabolic (n = 7), hematologic (n = 3), angioedema (n = 3), neurologic (n = 2), cardiovascular (n = 2) and 1 from each of psychiatric, reproductive, generalized edema problems. Conclusion: Gastrointestinal problems, particularly pancreatitis was the more frequently reported adverse drug reaction associated with GLP-1 agonist. The most adverse drug reactions were observed with liraglutide and exenatide. Highlights: GLP-1 receptor agonists are most commonly associated with gastrointestinal problems, particularly pancreatitis. Exenatide and liraglutide caused maximum ADRs, whereas albiglutide and lixisenatide caused minimum ADRs. Renal, dermatologic, hematologic, CVD, neurologic, autoimmune, hepatic and metabolic associated ADRs were identified.